Internalisasi Cinta terhadap Al-Qur’an dalam Pendidikan Karakter untuk Membangun Masyarakat Berkeadaban - Vahlepi, Sahrizal; Zulaika, Zulaika; Abidin, Zainal; Munawwaroh, Zahrotul (Indonesian Journal of Islamic Education and Local Culture, 2025)
This article explores the significance of love for the Qur’an as a foundational pillar in shaping individual character and fostering a successful and civilized society. In an increasingly complex socio-religious context, the internalization of Qur’anic values emerges as a strategic necessity to address the moral, social, and spiritual challenges facing the Muslim community. This study employs a qualitative approach through a literature review method, drawing upon a range of academic sources, the Qur’an, scholarly journals, and Islamic educational documents. The findings reveal that love for the Qur’an is expressed not only through its recitation and memorization but also through a deep understanding, appreciation, and application of its values in daily life. Both formal and informal education play a vital role in instilling Qur’anic values from an early age, through the family, schools, and the wider community. A collective strategy that involves individuals, educational institutions, communities, and government actors is essential for effectively implementing Qur’anic teachings within society. Therefore, love for the Qur’an significantly contributes to the development of morally upright individuals and the establishment of a just, inclusive, and civilized society. The study recommends strengthening Qur’anic literacy within educational systems and public policy as a concrete step toward building a sustainable Islamic civilization.